The effectiveness of video and pamphlets in influencing youth on environmental education - Ahmad, Jamilah; Sritharan, Gowri; Nasir, Nur Nasliza Arina Mohamad (Universiti Kebangsaan Malaysia, 2015)
Environmental problems are getting worse nowadays. The importance of Environmental Education, particularly to the youth is crucial because youth are the leaders of the future and play significant roles in determining the direction of the country. This study aims to explore the effectiveness of video and pamphlets in influencing youth on Environmental Education. This study also determines to find the best medium to educate youth on Environmental Education be it video or pamphlet. The Social Cognitive Theory by Albert Bandura was used as a theoretical framework and a qualitative method of focus group was carried out in order to collect data from respondents. Findings indicated that respondents had a higher preference for the video as an Environmental Education medium as opposed to pamphlets.